2017
DOI: 10.1371/journal.pone.0183054
|View full text |Cite
|
Sign up to set email alerts
|

Optimization of recombinant bacteria expressing dsRNA to enhance insecticidal activity against a lepidopteran insect, Spodoptera exigua

Abstract: Double-stranded RNA (dsRNA) has been applied to control insect pests due to its induction of RNA interference (RNAi) of a specific target gene expression. However, developing dsRNA-based insecticidal agent has been a great challenge especially against lepidopteran insect pests due to variations in RNAi efficiency. The objective of this study was to screen genes of chymotrypsins (SeCHYs) essential for the survival of the beet armyworm, Spodoptera exigua, to construct insecticidal dsRNA. In addition, an optimal … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
40
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
6

Relationship

3
3

Authors

Journals

citations
Cited by 51 publications
(48 citation statements)
references
References 42 publications
2
40
0
Order By: Relevance
“…Sonication treatment might impair the bacterial membrane through physical damage that results in leaks, through which the dsRNA in bacterial cells might be easily passed. Enhanced insecticidal activity by ultra‐sonication pretreatment has been observed in the application of dsRNA‐expressing bacteria to S. exigua . Thus, a dsRNA delivery system using recombinant bacteria pretreated with sonication can improve the insecticidal activity of dsRNA against lepidopteran insect pests.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Sonication treatment might impair the bacterial membrane through physical damage that results in leaks, through which the dsRNA in bacterial cells might be easily passed. Enhanced insecticidal activity by ultra‐sonication pretreatment has been observed in the application of dsRNA‐expressing bacteria to S. exigua . Thus, a dsRNA delivery system using recombinant bacteria pretreated with sonication can improve the insecticidal activity of dsRNA against lepidopteran insect pests.…”
Section: Discussionmentioning
confidence: 99%
“…Enhanced insecticidal activity by ultra-sonication pretreatment has been observed in the application of dsRNA-expressing bacteria to S. exigua. 34,38 Thus, a dsRNA delivery system using recombinant bacteria pretreated with sonication can improve the insecticidal activity of dsRNA against lepidopteran insect pests. This is the first study to report that dsRNA can be applied to control M.…”
Section: Discussionmentioning
confidence: 99%
“…On the other hand, a study performed with S. exigua used both live and heat‐killed transgenic E. coli cells expressing β1 integrin dsRNA. There was no difference in mortality rate (30–35%) with treatment using either live or heat‐killed bacteria . Thus, the susceptibility to RNAi effects with either live or killed bacteria might be species dependent.…”
Section: Strategies For Oral Administration Of Dsrna In Insects and Imentioning
confidence: 91%
“…There was no difference in mortality rate (30-35%) with treatment using either live or heat-killed bacteria. 105 Thus, the susceptibility to RNAi effects with either live or killed bacteria might be species dependent. A factor to consider is that the use of live bacteria as a sprayable form on plants might raise some safety concerns and, most likely, regulatory agencies will be hesitant to approve this method.…”
Section: Transformed Microorganisms and Virusesmentioning
confidence: 99%
“…Tian et al (2009) first reported the efficacy of bacterially expressed dsRNA in the induction of systemic RNAi in insects, in particular in the lepidopteran pest Spodoptera exigua. Several other studies have clearly shown that bacterial delivery (1) is cost-effective, (2) protects dsRNA molecules against degradation and (3) allows the development of new plant protection products/tools (Kim et al 2015;Lim et al 2016;Zhu et al 2016;Ganbaatar et al 2017;Israni and Rajam 2017;Vatanparast and Kim 2017;Wang et al 2018).…”
Section: Introductionmentioning
confidence: 99%